Cancer Chemoprevention: A Strategic Approach Using Phytochemicals - G., Mohan Shankar; Swetha, Mundanattu; Keerthana, C K; Rayginia, Tennyson P; Anto, Ruby John (Frontiers in Pharmacology, 2022)
Cancer chemoprevention approaches are aimed at preventing, delaying, or suppressing tumor incidence using synthetic or natural bioactive agents. Mechanistically, chemopreventive agents also aid in mitigating cancer development, either by impeding DNA damage or by blocking the division of premalignant cells with DNA damage. Several pre-clinical studies have substantiated the benefits of using various dietary components as chemopreventives in cancer therapy. The incessant rise in the number of cancer cases globally is an issue of major concern. The excessive toxicity and chemoresistance associated with conventional chemotherapies decrease the success rates of the existent chemotherapeutic regimen, which warrants the need for an efficient and safer alternative therapeutic approach. In this scenario, chemopreventive agents have been proven to be successful in protecting the high-risk populations from cancer, which further validates chemoprevention strategy as rational and promising. Clinical studies have shown the effectiveness of this approach in managing cancers of different origins. Phytochemicals, which constitute an appreciable proportion of currently used chemotherapeutic drugs, have been tested for their chemopreventive efficacy. This review primarily aims to highlight the efficacy of phytochemicals, currently being investigated globally as chemopreventives. The clinical relevance of chemoprevention, with special emphasis on the phytochemicals, curcumin, resveratrol, tryptanthrin, kaempferol, gingerol, emodin, quercetin genistein and epigallocatechingallate, which are potential candidates due to their ability to regulate multiple survival pathways without inducing toxicity, forms the crux of this review. The majority of these phytochemicals are polyphenols and flavanoids. We have analyzed how the key molecular targets of these chemopreventives potentially counteract the key drivers of chemoresistance, causing minimum toxicity to the body. An overview of the underlying mechanism of action of these phytochemicals in regulating the key players of cancer progression and tumor suppression is discussed in this review. A summary of the clinical trials on the important phytochemicals that emerge as chemopreventives is also incorporated. We elaborate on the pre-clinical and clinical observations, pharmacokinetics, mechanism of action, and molecular targets of some of these natural products. To summarize, the scope of this review comprises of the current status, limitations, and future directions of cancer chemoprevention, emphasizing the potency of phytochemicals as effective chemopreventives.